2018
DOI: 10.1212/wnl.0000000000006282
|View full text |Cite
|
Sign up to set email alerts
|

Serum neurofilament light

Abstract: Serum NfL holds promise as a biomarker for monitoring primary and secondary neuroaxonal injury after IS and for predicting functional outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
102
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 159 publications
(113 citation statements)
references
References 48 publications
10
102
1
Order By: Relevance
“…Results from MS populations have shown that increased levels of NfL in the CSF or blood were related to greater WM hyperintensity (WMH) volumes and gadolinium enhancing lesions ( Chitnis et al, 2018 ; Dalla Costa et al, 2019 ; Disanto et al, 2017 ; Kuhle et al, 2019 ). A similar pattern was found in patients with ischemic stroke ( Tiedt et al, 2018 ) and cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) ( Gravesteijn et al, 2019 ). Diffusion tensor imaging (DTI) is a particular form of diffusion-weighted imaging that characterizes the movement of water molecules in the brain and provides a way to examine microstructural changes of WM integrity.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Results from MS populations have shown that increased levels of NfL in the CSF or blood were related to greater WM hyperintensity (WMH) volumes and gadolinium enhancing lesions ( Chitnis et al, 2018 ; Dalla Costa et al, 2019 ; Disanto et al, 2017 ; Kuhle et al, 2019 ). A similar pattern was found in patients with ischemic stroke ( Tiedt et al, 2018 ) and cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) ( Gravesteijn et al, 2019 ). Diffusion tensor imaging (DTI) is a particular form of diffusion-weighted imaging that characterizes the movement of water molecules in the brain and provides a way to examine microstructural changes of WM integrity.…”
Section: Introductionsupporting
confidence: 70%
“…In addition to such overt damage, microstructural changes in WM can be assayed using DTI. There have been inconsistent results establishing whether CSF and blood levels of NfL are sensitive to such microstructural changes in WM detectable using DTI ( Menke et al, 2015 ; Mielke et al, 2019 ; Moore et al, 2018 ; Racine et al, 2019 ; Tiedt et al, 2018 ). When examining baseline DTI data using voxel-wise- and ROI-based approaches in MC we found that higher levels of serum NfL were negatively associated with FA, and positively associated with MD, RD, and DA throughout the entire cortex, although effects were strongest in posterior regions ( Table 2 and Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, following adjustment, the authors did not find a correlation between serum NF-L and infarct size on admission or mRS at 3 months. Tiedt et al (12) found NF-L levels to be increased in ischemic stroke patients at admission (<24 h), days 2, 3, and 7, and at 3 and 6 months post-stroke, with peak levels at day 7. NF-L levels at day 7 correlated with infarct volumes assessed by MRI and with mRS 3 months post-stroke, but after adjustment for age and hypertension, only NF-L levels obtained on days 3 and 7 correlated with infarct volume.…”
Section: Discussionmentioning
confidence: 98%
“…The inflammatory process that ensues after a stroke destabilizes the blood-brain barrier (BBB) and contributes to neuro-axonal damage, thereby increasing the release of NFs and glial and inflammatory markers into the CSF and blood (11). Ischemic stroke has recently been shown to cause persistent elevations in serum NF-L that correlated with infarct volumes and recurrent ischemic lesions (12). Furthermore, NF-L levels obtained within 24 h of symptom onset in the blood of ischemic stroke and TIA patients were associated with clinical severity on admission and TIA diagnosis, but not with infarct size or functional outcome at 3 months (13).…”
Section: Introductionmentioning
confidence: 99%
“…NF-L serum levels are higher in ischemic stroke cases than in healthy controls, while also differentiating between ischemic stroke and transient ischemic attack (Table 1). Higher NF-L levels were associated with more severe disability scores [44,45]. In a large prospective study, Pedersen et al used Simoa to study the association between functional outcome and serum NF-L levels sampled within the first 1-14 days, 3 months, and 7 years after ischemic stroke [41].…”
Section: Strokementioning
confidence: 99%